How have Cretan rivers responded to late Holocene uplift? A multi‐millennial, multi‐catchment field experiment to evaluate the applicability of Schumm and Parker's (1973) complex response model. Issue 9 (29th May 2022) - Macklin, Mark G.; Booth, Jonathan; Brewer, Paul A.; Tooth, Stephen; Duller, Geoff A.T.
Abstract: 'Complex response' (Schumm, 1973, Geomorphic thresholds and complex response of drainage systems. In Morisawa, M. (ed.), Fluvial Geomorphology . Binghamton: New York State University Publications: 299‐310) describes situations in which a single event triggers a series of progressively damped morphological and sedimentary adjustments within a catchment. Schumm and Parker's (1973, Implications of complex response of drainage systems for Quaternary alluvial stratigraphy. Nature 243: 99–100) classic stream table experiment of drainage system development showed that one baselevel fall event could result in formation of two sets of paired river terraces that need not be related to additional external (e.g., climate) influences. Despite its enduring popularity in fluvial geomorphology, large‐scale and long‐term field evaluations of Schumm and Parker's complex response model are very limited. Here, we report on a multi‐millennial, multi‐catchment field experiment in south‐western Crete where a high‐magnitude earthquake (estimated magnitude 8.3–8.5) on 21 July 365 ce resulted in up to 9 m of instantaneous uplift over a land area exceeding 6000 km 2 . Geomorphological, sedimentological, and chronological investigations were used to investigate the erosional and depositional histories in three catchments with outlets uplifted by the 365 ce event. These catchments were compared with the Anapodaris catchment in south central Crete where baselevel was not significantly affected by the earthquake. Although all uplifted catchments experienced valley floor incision, this occurred hundreds of years after 365 ce during a period of wetter climate. The number and age of trunk stream incision and aggradation phases are similar in both uplifted and non‐uplifted catchments, indicating that river responses following the 365 ce uplift event have not followed complex response trajectories in the form documented by Schumm and Parker (1973). This finding highlights the need for rigorous evaluation of other catchment or river response concepts, including through the combined use of laboratory experimental results, field data, and geochronology. In an era of rapid environmental change, characterizing and anticipating catchment and river system response increasingly will depend on a healthy interplay between different investigative approaches. Abstract : Schumm and Parker's (1973) classic experiment demonstrating river 'complex response' to baselevel change has provided an enduring model, but its field applicability has rarely been evaluated. In south‐western Crete, a 365 ce earthquake (land uplift up to c . 9 m) enables a multi‐millennial, multi‐catchment field evaluation of the model. Post‐uplift river terrace development was strongly conditioned by baselevel change but 'complex response' trajectories, as envisaged by Schumm and Parker, have not been followed. Instead, incision/aggradation phases have tracked regional hydroclimatic fluctuations